In silico characterisation of the complete Ly6 protein family in Fasciola gigantica supported through transcriptomics of the newly-excysted juveniles. (15th November 2021) - Davey, Sarah D.; Chalmers, Iain W.; Fernandez-Fuentes, Narcis; Swain, Martin T.; Smith, Dan; Abbas Abidi, Syed M.; Saifullah, Mohammad K.; Raman, Muthusamy; Ravikumar, Gopalakrishnan; McVeigh, Paul; Maule, Aaron G.; Brophy, Peter M.; et al.
Abstract : Incorporating the recently available F. gigantica genome, the current work revealed 20 novel Ly6 family members in F. gigantica and, in parallel, significantly extended the F. hepatica complement from 3 to 18 members. Abstract : Fasciola gigantica is one of the aetiological trematodes associated with fascioliasis, which heavily impacts food-production systems and human and animal welfare on a global scale. In the absence of a vaccine, fascioliasis control and treatment is restricted to pasture management, such as clean grazing, and a limited array of chemotherapies, to which signs of resistance are beginning to appear. Research into novel control strategies is therefore urgently required and the advent of 'omics technologies presents considerable opportunity for novel drug and vaccine target discovery. Here, interrogation of the first available F. gigantica newly excysted juvenile (NEJ) transcriptome revealed several protein families of current interest to parasitic flatworm vaccine research, including orthologues of mammalian complement regulator CD59 of the Ly6 family. Ly6 proteins have previously been identified on the tegument of Schistosoma mansoni and induced protective immunity in vaccination trials. Incorporating the recently available F. gigantica genome, the current work revealed 20 novel Ly6 family members in F. gigantica and, in parallel, significantly extended the F. hepatica complement from 3 to 18 members. Phylogenetic analysis revealed several distinct clades within the family, some of which are unique to Fasciola spp. trematodes. Analysis of available proteomic databases also revealed three of the newly discovered FhLy6s were present in extracellular vesicles, which have previously been prioritised in studying the host-parasite interface. The presentation of this new transcriptomic resource, in addition to the Ly6 family proteins here identified, represents a wealth of opportunity for future vaccine research.